Underwater Real-Time 3D Acoustical Imaging Theory, Algorithm and System Design - Chi, Cheng (Signals and Communication Technology, 2019)
This book presents the topic of underwater real-time 3-D acoustical imaging covering the theory, algorithms and system design. It summarizes recent advances in wideband and ultra-wideband underwater real-time 3-D acoustical imaging, which will be very useful for developing next-generation systems. Through simulation techniques, readers are able to quickly learn and develop practical underwater real-time 3-D acoustical imaging systems of their own.